Outcomes of paediatric malarial hepatopathy: a study from Eastern India - Pradhan, Subal Ku.; Mutalik, Pawan; Subudhi, Tirumal; Swain, Arakhita; Mohanty, Niranjan (Paediatrica Indonesiana, 2014)
Background Severe malaria causes multi-organ involvement , including hepatic dysfunction.Jaundice in severe malaria is found more commonly in adults than in children. It is important to assess the factors associated with malarial hepatopathy, the varied clinical presentations, as well as the complications in order to initiate early interventional measures. There are a limited number of studies in the pediatric population on malarial hepatopathy. Objective To assess the factors associated with malarial hepatopathy, the varied clinical presentations, as well as its complications. Methods This prospective study was conducted in the Department of Paediatrics, Sardar Vallabh Bhai Patel Post Graduate Institute of Paediatrics (SVPPGIP), Cuttack, Odisha, India from January 20 10 to June 2013, and included 70 children with malaria and jaundice, aged 6 months to 14 years. Malaria was confirmed by microscopic examination of blood smears. Detailed clinical evaluations and investigation s were carried out to find multi-organ afflictions, with a special emphasis on hepatic involvement. Results Of218 children with malaria admitted during this period, 70 (32%) children had fever and jaundice on presentation. All children who had both Plasmodium faldparum and vivax infection had malarial hepatopathy. Complications, including acute kidney injury (AKI), disseminated intravascular coagulation (DIC), cerebral malaria, and mortality, were significantly higher among children with malarial hepatopathy compared to children without hepatopathy. Howevei; there was no significant difference of hypoglycemia, respiratory distress syndrome (RDS), convulsions or severe anemia, between children with and without hepatopathy. Conclusion Hepatopathy is more common with mixed malaria infections. The incidence of AKI, DIC, cerebral malaria, and mortality are significantly higher in patients with hepatopathy. Malarial hepatopathy should be considered in patients presenting with acute febrile illness and jaundice so that specific treatment can be initiated early to prevent increased morbidity and mortality.